Radykalne innowacje czy nastawienie na ewolucyjne zmiany - przejawy innowacyjności regionalnych browarów w Polsce - Jasińska, Alicja; Jasiński, Bartosz (The radical innovations or putting on evolutionary changes - the symptoms of innovations of regional breweries in Poland, 2006)
The article underlines meaning of every kind of innovation: both evolutionary character the same as and revolutionary for realization of strategy of development enterprises, with category the MSP, in peculiarity the regional breweries in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 362-368